Peran Collaborative Governance dalam Implementasi CSR BUMN untuk Peningkatan Inklusi Keuangan pada Masyarakat Rentan : Studi Kasus Bank BRI Cabang Jombang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the role of Collaborative Governance in the implementation of Corporate Social Responsibility (CSR) by Bank BRI Jombang Branch as an alternative strategy to enhance financial access. Utilizing the theoretical framework of Ansell and Gash, this study examines how the dimensions of starting conditions, facilitative leadership, and institutional design influence the effectiveness of inter-actor synergy in bridging access gaps that are unreachable through single-actor approaches. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with bank management, village officials, and community leaders, supported by field observations and document analysis. The findings indicate that collaboration effectively mitigates information asymmetry and credit risks through a trust-based